2000
DOI: 10.1677/jme.0.0250053
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of retinoic acid on the development of immature porcine granulosa cells to mature cells

Abstract: The present study investigated the effect of retinoic acid (RA) on the differentiation of granulosa cells prepared from porcine ovaries. The granulosa cells were precultured for 15 h, then cultured for 48 h with FSH and further treated for 24 h with LH in order to induce their transformation into luteal cells. After the cells had been exposed to 1 µM retinoids (RA, retinal and retinol) for 87 h, analysis of the LH receptor mRNA expression, an indicator of granulosa cell differentiation, was carried out by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…The MK gene product could be an intermediary in the above reported developmental phenomena (Griffith and Zile, 2000). In rat granulosa cells, 0.3 mM RA resulted in a two fold increase in MK mRNA levels (Minegishi et al, 1996), and 1 mM RA altered LH receptor mRNA expression (Hattori et al, 2000). The embryotrophic effects of MK reported by Ikeda et al (2000a,b) reproduce in part the effect of RA within the present work.…”
Section: Discussionsupporting
confidence: 80%
“…The MK gene product could be an intermediary in the above reported developmental phenomena (Griffith and Zile, 2000). In rat granulosa cells, 0.3 mM RA resulted in a two fold increase in MK mRNA levels (Minegishi et al, 1996), and 1 mM RA altered LH receptor mRNA expression (Hattori et al, 2000). The embryotrophic effects of MK reported by Ikeda et al (2000a,b) reproduce in part the effect of RA within the present work.…”
Section: Discussionsupporting
confidence: 80%
“…These results are consistent with previous reports (Deb et al, 2011;Gómez et al, 2003). The beneficial effects of RA during IVM are mediated by enhancing oocyte maturation through its effect on FSH or LH receptor expression (Hattori et al, 2000), increasing mRNA quality and processing (Gomez et al, 2004), growth factors signaling by endogenous oxidative-stress protection mechanism (Guerin, 2001) and /or prevention of apoptosis (Deb et al, 2011). …”
Section: Resultssupporting
confidence: 92%
“…These authors found antiproliferative and pro-apoptotic effects that mainly targeted the ICM [17]. Concentrations of ATRA between 0.3 mM and 1 mM are commonly encountered in the literature on reproductive cells [9,18,19]. Finally, a concentration of 1 mM ATRA during IVM can improve blastocyst development (Ikeda S, personal communication).…”
Section: Discussionmentioning
confidence: 99%